2006
DOI: 10.1007/s10526-005-5252-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of floral and extrafloral resources on predation of Aphis spiraecola by Harmonia axyridis on Apple

Abstract: Flowering companion plants and plants producing extrafloral nectar are being proposed to enhance biological control in apple (Malus domestica Borkh.) orchards. This experiment evaluated the impact of floral and extrafloral resources on predation of spirea aphid (Aphis spiraecola Patch) on apple by adult Harmonia axyridis (Pallas) under greenhouse conditions. Predation of spirea aphids was not affected by the presence of flowering buckwheat (Fagopyrum esculentum) as compared with either buckwheat with flowers r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 25 publications
0
26
0
5
Order By: Relevance
“…A laboratory study showed that over a period of 4 hours, there was less biological control of spirea aphid in the presence of peach shoots bearing extrafloral nectar than in the presence of no additional food sources or in the presence of buckwheat flowers (Fagopyrum esculentum) (Spellman et al, 2006). We also found that interplanting 50% of an apple orchard with extrafloral nectar-providing fruit trees reduced the amount of biological control of rosy apple aphid (Dysaphis plantaginea) by adult H. axyridis in a field test (Brown & Mathews, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A laboratory study showed that over a period of 4 hours, there was less biological control of spirea aphid in the presence of peach shoots bearing extrafloral nectar than in the presence of no additional food sources or in the presence of buckwheat flowers (Fagopyrum esculentum) (Spellman et al, 2006). We also found that interplanting 50% of an apple orchard with extrafloral nectar-providing fruit trees reduced the amount of biological control of rosy apple aphid (Dysaphis plantaginea) by adult H. axyridis in a field test (Brown & Mathews, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, plant cover had nil effect on the pear psyllid control. Some studies have reported a decrease in herbivore density in the presence of ground cover vegetation (AguilarFenollosa et al, 2011;Altieri and Schmidt, 1986;Beizhou et al, 2011;Irvin et al, 2006;Pfammatter and Vuignier, 1998;Rieux et al, 1999;Wyss, 1995;Wyss et al, 1995) et al, 1982;Meyer, 1990a, 1990b;Spellman et al, 2006). All of these studies have shown that selection of the plant cover species in the orchard is important in preventing increased pest population.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional requirements for development of MALB were studied by Agarwala et al ( 2008 ) . To some extent, MALB can compensate for low prey availability by feeding at extrafl oral nectaries and the presence of such nectaries may interfere with biological control (Spellman et al 2006 ) . Presence of aphids enhances mate-fi nding behavior of MALB males, and receptivity to mating by females (Obata 1997 ) .…”
Section: Biologymentioning
confidence: 99%